1998
DOI: 10.1046/j.1365-3059.1998.00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of the resistance of Erysiphe graminis f.sp. hordei to five triazole fungicides

Abstract: The genetics of resistance to ergosterol demethylation inhibitor (DMI) fungicides of the triazole (conazole) group was examined in a cross between two isolates of the barley powdery mildew fungus, Erysiphe graminis (¼ Blumeria graminis) f.sp. hordei. One isolate, E1, was previously identified as being resistant to the triazole fungicide triadimenol, while the other, HL3/5, was sensitive. The 56 progeny tested were classified into two distinct groups, either being resistant to triadimenol, like E1, or sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…However, PR1 and PR11 were obtained from the same geographic area of northern France, so they may have been subject to similar selection pressures. Evidence for monogenic resistance to DMI fungicides has also been reported for resistance to triadimenol in Erysiphe graminis (4,5), triadimenol in Nectria haematococca (9,24), ketoconazole in Neurospora crassa (39), and fenarimol in Venturia inaequalis (40). This contrasts with reports of resistance to the fungicides imazalil in Aspergillus nidulans, fenarimol in N. haematococca (24), triadimenol in E. graminis (22), propiconazole in Pyrenophora teres (34), and triadimefon in Ustilago maydis (41), in which DMI resistance was polygenic in nature.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, PR1 and PR11 were obtained from the same geographic area of northern France, so they may have been subject to similar selection pressures. Evidence for monogenic resistance to DMI fungicides has also been reported for resistance to triadimenol in Erysiphe graminis (4,5), triadimenol in Nectria haematococca (9,24), ketoconazole in Neurospora crassa (39), and fenarimol in Venturia inaequalis (40). This contrasts with reports of resistance to the fungicides imazalil in Aspergillus nidulans, fenarimol in N. haematococca (24), triadimenol in E. graminis (22), propiconazole in Pyrenophora teres (34), and triadimefon in Ustilago maydis (41), in which DMI resistance was polygenic in nature.…”
Section: Discussionmentioning
confidence: 88%
“…Early reports, based mainly on the use of laboratory mutants, suggested that resistance had a polygenic basis, with a complex heritable pattern involving additive genetic factors (10,35). However, later studies involving isolates derived from field locations indicated that resistance was largely controlled by single major genes (4,5,34,40). The present study used sexual crosses to investigate the genetic control of resistance to the DMI fungicide prochloraz in field isolates of the cereal eyespot pathogen T. yallundae.…”
Section: Discussionmentioning
confidence: 91%
“…Four distinct resistance phenotypes, to the DMI fungicide triadimenol (TDL), have been observed in UK populations of Bgh (Blatter et al, 1998;Brown and Wolfe, 1991;: low, medium, high, and very high resistance, the latter withstanding doses above those recommended for Weld use. In crosses between a sensitive isolate of Bgh and isolates with the three highest levels of resistance, one major gene controlled resistance in each case (Blatter et al, 1998;Brown, 1996;Brown et al, , 1996.…”
Section: Introductionmentioning
confidence: 99%
“…In crosses between a sensitive isolate of Bgh and isolates with the three highest levels of resistance, one major gene controlled resistance in each case (Blatter et al, 1998;Brown, 1996;Brown et al, , 1996. Linkage analysis of TDL response genes to avirulence genes indicated that at least two loci control TDL resistance, the medium resistance of isolate CC107 being at a diVerent locus from the high and very high resistances of isolates E1 and CC138, and CC146, respectively (Brown, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple applications of mancozeb alone were not as effective as the acibenzolar-S-methyl + mancozeb combination (efficacy trial 2), suggesting a possible synergistic effect. Resistance to DMI fungicides has been reported for a range of pathogens overseas (Blatter et al 1998;Leroux et al 2000;Karaoglanidis et al 2002) andin Australia (O'Brien 1994;Wallwork 1995), so it is possible that isolates of C. africana resistant to DMI could develop in Australia with repeated applications of triadimenol. A combination of acibenzolar-S-methyl and mancozeb offers a cost-effective alternative to the triazoles, should such resistant isolates develop.…”
Section: Discussionmentioning
confidence: 99%